Do Biomarkers Of Inflammation, Monocyte Activation And Altered Coagulation Explain Excess Mortality Between HIV Infected and Uninfected People? - So-Armah, Kaku A; Tate, Janet P; Chang, Chung-Chou H; Butt, Adeel A; Gerschenson, Mariana; Gibert, Cynthia L; Leaf, David; Rimland, David; Rodriguez-Barradas, Maria C; Budoff, Matthew J; Samet, Jeffrey H; Kuller, Lewis H; et al. (Journal of acquired immune deficiency syndromes (1999), 2016)
HIV infection and biomarkers of inflammation (measured by interleukin-6 [IL-6]), monocyte activation (soluble CD14 [sCD14]), and coagulation (D-dimer) are associated with morbidity and mortality. We hypothesized that these immunologic processes mediate (explain) some of the excess risk of mortality among HIV infected (HIV+) versus uninfected people independently of co-morbid diseases.